Joint effect of multi-factorial studies on the creative behaviour of secondary school students in selected states of Nigeria (2011)
This study investigated the joint influence which factors like environments, attitudinal disposition of parents, attitudinal disposition of teachers and peer pressure have on the creative behavior of secondary school students. The study is descriptive in nature, and it adopted the "ex-post facto" design. Stratified random sampling technique was used for the selection of 1,800 respondents out of2,620 representing 69 percent of the total population. The mean age for the participants was 13.49 years. Data were collected using two valid and reliable research instruments namely; Ibadan Creativity Assessment Scale, (ICAS a=0:76) and Creative Behavior Determinant Scale, (CBDS a =0.84). The data were analyzed using Multiple Regression and Analysis of variance. The findings showed that environment, attitudinal disposition of parents, teachers' attitudinal disposition and peer pressure significantly influenced creative behavior of the subjects (F(4; 1795) = 298.985; P<.05). The total variance accounted for by the four independent variables taken together was 39.9 percent (i.e multiple R2=z.399). The result indicated that when talking about students' creative behavior the four factors are quite relevant towards its determination. Furthermore, an adjusted R2 value of .399 obtained showed that 39.9% of the total variations in students' creative behavior is accounted for by the four independent variables taken together. The renaming 60.1% is due to other factors. The standard error of these estimates is 72.70355. Analysis of variance on Table 2 revealed that the adjusted R2 value was significant at 0.05. This showed that the adjusted R2 value was not due to chance.